Komunikasi Identitas dan Hibriditas Budaya Tionghoa Muslim: Kajian Analisis Wacana pada Media Online Indonesia - Erita Riski Putri; Rezzi Nanda Barizki (JKOMDIS : Jurnal Ilmu Komunikasi Dan Media Sosial, 2026)
Muslim Chinese in Indonesia are placed in a liminal space between two sets of identity systems which have been historically antagonistic to each other: Chinese ethnicity and Islam. The visible emergence of the community in the public sphere has attracted more and more attention, however, the representation of their hybrid identity in the Indonesian online media has yet to be critically analyzed, especially in the field of discourse analysis. The current literature tends to tackle this issue from the sociological or ethnic literature, failing to offer much analysis of the representation of this community in the mainstream online media discourse. The study aims to analyze the representation of the hybrid identity of the Muslim Chinese community within the negotiation between ethnicity and religiosity aspects of the Muslim Chinese community through language used and news framing; discourse productions in cross-media with different ideological aspects; and the power relations behind the productions of the discourse of the Muslim Chinese community. This study is conducted through the qualitative approach using the Fairclough's Three-Dimensional Critical Discourse Analysis (CDA) Model (textual dimension, discourse practice dimension, and social practice dimension) and the article text data taken from six websites, including newspapers, magazines, and blogs belonging to three different ideological levels from 2020 until 2026, totaling 15 articles. The five recurring discursive patterns that emerged were: hybridity is presented as an instrumental function; community identity is wholly religious; there are no conflicting or ambiguous representations of identity; organisational elites and state officials' voices are in control; and hybridity is enacted in the material, with artworks and physical spaces. The uniformity of these patterns suggests the domestication of Bhabha's ‘Third Space', where ambivalence of identity is refuted as a symbol of harmony 'consumeable' by the general public, thus, signifying a systematic discursive construction (not neutral) in the representation of this dual minority community.